2013
DOI: 10.1371/journal.pone.0081708
|View full text |Cite
|
Sign up to set email alerts
|

Pathway and Mechanism of pH Dependent Human Hemoglobin Tetramer-Dimer-Monomer Dissociations

Abstract: Hemoglobin dissociation is of great interest in protein process and clinical medicine as well as in artificial blood research. However, the pathway and mechanisms of pH-dependent human Hb dissociation are not clear, whether Hb would really dissociate into monomers is still a question. Therefore, we have conducted a multi-technique investigation on the structure and function of human Hb versus pH. Here we demonstrate that tetramer hemoglobin can easily dissociate into dimer in abnormal pH and the tetramer → dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 34 publications
6
27
0
2
Order By: Relevance
“…Note that although alpha and beta globin are listed separately, they were contained within one sample of hemoglobin. MS measurement confirmed that under conditions used hemoglobin was dissociated into monomers, in agreement with literature , and it was considered as an equimolar mixture of alpha and beta globins.…”
Section: Resultssupporting
confidence: 87%
“…Note that although alpha and beta globin are listed separately, they were contained within one sample of hemoglobin. MS measurement confirmed that under conditions used hemoglobin was dissociated into monomers, in agreement with literature , and it was considered as an equimolar mixture of alpha and beta globins.…”
Section: Resultssupporting
confidence: 87%
“…Consequently, we have to interpret the low number of interacting spin pairs to be a consequence of protein dissociation on the BC surface. A similar dissociation has been observed at extreme pH values (below 6.5 and above 8.0), or for low sample concentrations (<100 μ m ) …”
Section: Resultssupporting
confidence: 78%
“…This means that dissociation happens either at the α 1 β 2 /α 2 β 1 or at the α 1 β 1 /α 2 β 2 sliding interfaces. The α and β subunits interact along the α 1 β 1 (α 2 β 2 ) packing interface by forming tight contacts involving approximately 34 residues, whereas the α 1 β 2 (α 2 β 1 ) sliding interface involves only about 19 residues . The formation of α 1 β 1 and α 2 β 2 is therefore more likely .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations